2020
DOI: 10.3389/fimmu.2020.558036
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Omega-6 Fatty Acid Docosapentaenoic Acid Positively Modulates Brain Innate Immune Response for Resolving Neuroinflammation at Early and Late Stages of Humanized APOE-Based Alzheimer's Disease Models

Abstract: Neuroinflammation plays a crucial role in the development and progression of Alzheimer's disease (AD), in which activated microglia are found to be associated with neurodegeneration. However, there is limited evidence showing how neuroinflammation and activated microglia are directly linked to neurodegeneration in vivo. Besides, there are currently no effective anti-inflammatory drugs for AD. In this study, we report on an effective anti-inflammatory lipid, linoleic acid (LA) metabolite docosapentaenoic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Docosahexaenoic acid reduces surface presentation of TLR4 and CD14, thereby inhibiting LPS-induced downstream signaling and associated proinflammatory responses [ 219 , 220 ]. Additionally, dietary docosapentaenoic acid restrains microglia-mediated neuroinflammation and promotes neuronal survival in AD mouse models [ 368 ]. In accordance, omega-3 PUFA supplementation reduces microglial inflammatory activation and mitigates neural tissue destruction after traumatic brain injury [ 369 , 370 ].…”
Section: Mechanisms Mediating Obesity-associated Neuroinflammationmentioning
confidence: 99%
“…Docosahexaenoic acid reduces surface presentation of TLR4 and CD14, thereby inhibiting LPS-induced downstream signaling and associated proinflammatory responses [ 219 , 220 ]. Additionally, dietary docosapentaenoic acid restrains microglia-mediated neuroinflammation and promotes neuronal survival in AD mouse models [ 368 ]. In accordance, omega-3 PUFA supplementation reduces microglial inflammatory activation and mitigates neural tissue destruction after traumatic brain injury [ 369 , 370 ].…”
Section: Mechanisms Mediating Obesity-associated Neuroinflammationmentioning
confidence: 99%
“…As a member of the long-chain polyunsaturated fatty acid family, DPA could decrease the mRNA expression of inflammatory factor and microglial markers. 43,44 Previous research demonstrated that DPA could improve the damage caused by Aβ and tau in 3xTg-AD mice by the PS1 presenilin pathway, 45 and correlation analysis showed that DPA is positively correlated with Firmicutes, Bifidobacterium , and Aerococcus. These findings reveal that HF-M might increase the DPA level by increasing the proportions of the Firmicutes and Bifidobacterium , thus improving cognitive disorders and reducing Aβ deposition in AD mice.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the long-chain polyunsaturated fatty acid family, DPA could decrease the mRNA expression of inflammatory factor and microglial markers. 43,44 Previous research demonstrated that DPA could improve the damage caused by Aβ and tau in 3xTg-AD mice by the PS1 presenilin pathway, 45 and correlation analysis showed that DPA is positively correlated with Firmicutes, Bifidobacterium, and…”
Section: Papermentioning
confidence: 99%
“…Mushrooms contain about 4% to 9% of soluble fibers as well as 22% to 30% of insoluble fibers. Previous studies have revealed that 100 grams of P. ostreatus mushroom contain 4.1 grams of dietary fibers [ 43 ].…”
Section: Chemicals In Edible Mushroomsmentioning
confidence: 99%